Association between thermal condition, thermal acceptability and student's performance in naturally ventilated classroom for school building enhancement - Hariri, Azian; Idris, Ahmad Fu’ad; Nasir, Nurul Fitriah; Nordin, Normayati (Penerbit UTHM, 2020)
Malaysian comfort standard based on the MS 1525: 2019 have established for acceptable indoor conditions for comfort cooling in non- residential building. However, no comfort standard for young children had yet been established. Determinants of thermal comfort were assumed to be similar for both children and adults. However, metabolic rate, clothing and limited adaptive behaviour of children may cause differences. The new ASHRAE comfort standard 55-2013 specifies an extension of naturally ventilation standard with elevated air movement up to 0.8 m/s (without personal control) and 1.2 m/s (with personal control). Malaysia has high temperature, high humidity level, and the usage of only ceiling fans in the school buildings may result in the needs of higher air movement than the limit specified by ASHRAE 55-2013 standard. It has been established that thermal comfort is vital to student's perception, health and performance. A conducive classroom should consider both the thermal acceptability range and its effect on the performance of the students. Thus, this study aims to study the relation of thermal acceptability with student's performance and enhance the thermal comfort condition of students in the classroom with ceiling fans through CFD analysis. Physical measurement parameters such as indoor temperature, air velocity, relative humidity and, mean outdoor temperature will be measured along with subjective measurement on thermal acceptability, and performance assessments. ..